Enhancing soil microbiome resilience: the mitigating role of silicon against environmental stresses - Etesami, Hassan (Frontiers in Agronomy, 2024)
The soil microbiome plays a pivotal role in the functioning and resilience of agricultural ecosystems, contributing to critical processes such as organic matter decomposition, nutrient cycling, and plant growth promotion. However, the soil microbiome is constantly challenged by various environmental stresses, including drought, heavy metal contamination, salinity, and climate change, which can significantly disrupt the delicate balance of the soil ecosystem. In this context, the application of silicon (Si) has emerged as a promising strategy to mitigate the adverse effects of these environmental stresses on the soil microbiome. This review paper synthesizes the current understanding of the impacts of environmental stresses on the soil microbiome and explores the potential of Si as a mitigating agent in enhancing the resilience of the soil microbial community. Silicon can enhance the resilience of the soil microbiome through several mechanisms, such as increasing soil pH, improving nutrient and water availability and uptake, altering root exudation patterns and plant physiology, and directly stimulating the abundance, diversity, and functional potential of key microbial groups. By enhancing the resilience of the soil microbiome, Si application can help maintain the critical ecosystem services provided by soil microorganisms, ultimately contributing to the sustainability and productivity of agricultural systems. The review also highlights future research aspects, including elucidating the precise mechanisms of Si-microbiome interactions, evaluating the long-term effects of Si on soil microbiome resilience, optimizing Si application strategies for specific crop-soil systems, integrating Si management with other sustainable soil practices, and assessing the impacts of Si on soil microbiome-mediated ecosystem services.